Bayt Al-Hikmah dan Revolusi Intelektual Islam: Transfer Ilmu sebagai Fondasi Kejayaan Abbasiyah - Ernawati Ernawati; Ismail Ismail; Adlan Fauzi Lubis (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
This article examines the role of Bayt al-Hikmah in shaping the Islamic intellectual revolution during the Abbasid era through the transfer, adaptation, and transformation of knowledge derived from the Greek, Persian, and Indian traditions. The study aims to explain the mechanisms of the translation movement, the integration of philosophical rationality with the Islamic sciences, and the emergence of Al-Kindī, Al-Khwārizmī, and Al-Farabi as indicators of successful epistemic transformation. This research employs a qualitative approach using library research and historical-critical analysis. The data were drawn from books, journal articles, academic encyclopedias, and historiographical studies addressing the Abbasid dynasty, Bayt al-Hikmah, the translation movement, Islamic philosophy, and the history of science. The data were analyzed through source selection, external and internal criticism, thematic categorization, historical interpretation, and argumentative synthesis. The findings demonstrate that Bayt al-Hikmah functioned not merely as a library or translation center, but as an institutional nexus connecting state patronage, multilingual translators, and interreligious scholarly communities. Knowledge transfer occurred through the stages of adoption, terminological adaptation, methodological internalization, and innovation. The integration of logic and philosophy strengthened Islamic theology, uṣūl al-fiqh, Qur’anic exegesis, and other scholarly traditions without diminishing the authority of revelation. The emergence of Abbasid scholars further demonstrates that foreign knowledge was transformed into new theories, methods, and technologies. The article concludes that Abbasid intellectual flourishing rested on epistemic openness, institutional support, a strong culture of literacy, and the critical capacity to engage with knowledge across civilizations.